From the forest to the plate – Hemicelluloses, galactoglucomannan, glucuronoxylan, and phenolic-rich extracts from unconventional sources as functional food ingredients. (1st July 2022) - Granato, Daniel; Reshamwala, Dhanik; Korpinen, Risto; Azevedo, Luciana; Vieira do Carmo, Mariana Araújo; Cruz, Thiago Mendanha; Marques, Mariza Boscacci; Wen, Mingchun; Zhang, Liang; Marjomäki, Varpu; Kilpeläinen, Petri
Graphical abstract: Highlights: Forest industry side-streams showed antiviral, antioxidant and antidiabetic potential. Both wood hemicelluloses and bark polyphenols decreased erythrocyte hemolysis. Bark polyphenols protected against Coxsackievirus A9 infection. Cell-based experiments showed non-toxic in vitro profile of extracts. Abstract: This study aimed to characterise pressurised hot water (PHW) extracts from nonconventional sources of functional carbohydrates and phenolic compounds in terms of antioxidant capacity, antiviral activity, toxicity, and human erythrocytes' protection antidiabetic potential. PHW extracts of Norway spruce bark (E1 + E2) and Birch sawdust (E3 + E4) contained mostly galactoglucomannan and glucuronoxylan. In contrast, samples E5 to E9 PHW extracted from Norway spruce, and Scots pine bark are rich sources of phenolic compounds. Overall, phenolic-rich extracts presented the highest inhibition of α-amylase and α-glucosidase and protection against stable non-enveloped enteroviruses. Additionally, all extracts protected human erythrocytes from hemolysis. Cell-based experiments using human cell lines (IMR90 and A549) showed extracts' non-toxic in vitro profile. Considering the relative toxicological safety of extracts from these unconventional sources, functional carbohydrates and polyphenol-rich extracts can be obtained and further used in food models.